Analisis Manajemen Pengelolaan Keuangan: Studi Kasus di SMA Muhammadiyah 1 Blitar - Abdul Rozak Ali Maftuhin; Sunarto Sunarto (STIKes Ibnu Sina Ajibarang, 2025)
The cost of education is a crucial component in the implementation of education, as the educational process cannot proceed without financial support. This study aims to describe the collection and management of finances at SMA Muhammadiyah 1 Blitar. The research approach used is qualitative research with a case study design. The researcher conducted interviews with the school principal and treasurer, document analysis, and observations. The results of the study show that school finances are sourced from government assistance, such as BOS (School Operational Assistance) and BPOPP (Operational Assistance for Education Funding), tuition fees (SPP), development fees (DPP), the foster parents' movement program, and donations from Lazismu. In the aspect of financial management, the school implements mechanisms for planning, execution, recording, reporting, and accountability while adhering to the principles of transparency, accountability, effectiveness, and efficiency.